Interpretation and Performance Practice on Debussy’s Nocturne for Piano - Sookkho, Korrapat; Chulapan, Panjai (Rangsit Music Journal, 2024)
This research article is about the interpretation and performance practice of Nocturne for Piano by Claude Debussy (1862-1918). The research aims to study Debussy’s biography, the history of the Nocturne as well as the interpretation and playing techniques of the Nocturne. The composition contains beautiful melodies, varieties of harmonies and tonality changes. The overall atmosphere is ambiguous in the perspective of tonality and harmony as in most of the impressionism music. However, the composer has presented the melody line clearly. In addition, noticeable compositional techniques such as two-against-three usage in melody and accompaniment and pedal usage. Pianists should control sound quality by carefully choosing finger numbers for each phrase and controlling the pedal to create vague atmospheres and tone color to meet the composer’s purpose along with practicing different techniques to present the appropriate sound and atmospheres. The result of the study shows that when the pianist is able to control the tone color and pedal usage, the pianist can clearly and beautifully express the feeling of the composition.